Strategy and the business landscape (Prentice Hall, 2006)
Pankaj Ghemawat, in collaboration with Bruno Cassiman, David Collis and Jan Rivkin, has prepared the second edition of an introductory strategy textbook that adopts a value-focused, firm-centered perspective on strategy. The book is meant to be rigorous in its research base, pragmatic in its focus, and concise. The second edition includes new, full-length chapters on competitive dynamics (with Bruno Cassiman) and on corporate strategy (with Jan Rivkin).